Kemiskinan Perdesaan dan Perkotaan: Sebuah Literature Review - Istyawan, Aryohaji (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Poverty is still a major challenge faced by people in various parts of the world, including Indonesia. This problem has serious consequences for those who live in rural and urban areas. This research was conducted to comprehensively examine and analyze rural and urban poverty. This research uses the literature review method. This method is carried out by tracing reading sources to produce scientific articles on rural and urban poverty with a focus on problems, groups, causes, impacts, and program policies in Indonesia. The research steps start from identifying reading sources, collecting data, and analyzing data. The findings of this literature review are in the form of an in-depth analysis of the problems of rural and urban poverty, poor community groups in rural and urban areas, causes of rural and urban poverty, impacts of rural and urban poverty, and policies for programs to address rural and urban poverty. The conclusion of this research is that rural and urban poverty have their own characteristics even though there is a close relationship. In addition, the presence of the concept of rural and urban poverty is expected to be a recommendation to be integrated into poverty alleviation by various parties especially the government and academics in Indonesia.